2023
DOI: 10.1021/acs.jnatprod.3c00041
|View full text |Cite
|
Sign up to set email alerts
|

Euphohelides A–C, ent-Abietane-Type Norditerpene Lactones from Euphorbia helioscopia and Their Anti-Inflammatory Activities

Abstract: Three unreported ent-abietane-type norditerpene lactones, euphohelides A−C (1−3), and 11 known analogs (4− 14) were isolated from the whole plants of Euphorbia helioscopia L. Euphohelide A (1) is an unprecedented 2-nor-ent-abietane lactone bearing a unique 5/6/6/5 tetracyclic system. Euphohelides B (2) and C (3) possess 2-nor-6/6/6/5 and 2,3-dinor-5/6/6/5 dilactone tetracyclic moieties, respectively. Their structures were established by spectroscopic methods, computational ECD, and X-ray crystallographic analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The anti‐inflammatory effects of 1 — 28 were evaluated by testing their inhibitory effects on NO production induced by lipopolysaccharide in RAW 264.7 macrophages using the Griess assay (Figure S2). [ 40‐41 ] The results (Table 1) showed that compounds 3 , 10 — 12 , 19 — 22 , 24 , 25 , and 27 exhibited notable inhibitory activities (IC 50 < 25 μmol/L, cell viability over 98% at 40 μmol/L), surpassing the potency of the positive control N G ‐Monomethyl‐ l ‐ arginine ( l ‐NMMA) (IC 50 = 26.12 ± 2.03 μmol/L). In particular, the IC 50 values of compounds 19 — 21 and 25 were less than 10 μmol/L (7.89 ± 0.44, 6.25 ± 0.46, 2.98 ± 0.29, and 3.60 ± 0.28 μmol/L).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The anti‐inflammatory effects of 1 — 28 were evaluated by testing their inhibitory effects on NO production induced by lipopolysaccharide in RAW 264.7 macrophages using the Griess assay (Figure S2). [ 40‐41 ] The results (Table 1) showed that compounds 3 , 10 — 12 , 19 — 22 , 24 , 25 , and 27 exhibited notable inhibitory activities (IC 50 < 25 μmol/L, cell viability over 98% at 40 μmol/L), surpassing the potency of the positive control N G ‐Monomethyl‐ l ‐ arginine ( l ‐NMMA) (IC 50 = 26.12 ± 2.03 μmol/L). In particular, the IC 50 values of compounds 19 — 21 and 25 were less than 10 μmol/L (7.89 ± 0.44, 6.25 ± 0.46, 2.98 ± 0.29, and 3.60 ± 0.28 μmol/L).…”
Section: Resultsmentioning
confidence: 99%
“…The quantum chemical ECD calculations were performed by Gaussian 16 as previously reported. [ 40‐41 ] Details were provided in the Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
“…Due to the small amount of 2, we tested the inhibitory effects of compounds 1 and 3-8 on NO production in LPSinduced RAW264.7 cells to evaluate their anti-inflammatory activities. [19,20] The results showed that all the tested ent-atisane diterpenoids exhibited inhibitory effects against NO production at a concentration of 40 μM. In particular, compounds 4, 7, and 8 showed better inhibitory activities against NO production with the inhibition rate of 54.95 %, 52.95 %, and 54.61 %, respectively (Figure 7A).…”
Section: Resultsmentioning
confidence: 99%
“…[12,15] As part of our efforts to search for antiinflammatory lead compounds from traditional Chinese medicine, three ent-abietane norditerpene lactones have been isolated from the anti-inflammatory fraction extracted from the whole plant of E. helioscopia. [19] In an ongoing investigation, three unreported ent-atisane diterpenoids (1-3) together with five known ones (4-8) were obtained from the bioactive fraction (Figure 1). Among these, compounds 4, 7, and 8 exhibited significant inhibitory effects on LPS-induced Nitric Oxide (NO) production in a dose-dependent manner.…”
Section: Introductionmentioning
confidence: 98%
“…The absolute configuration of euphofischeroid I (9) was finally delineated as (2R,3S,4S,7R,9S,11R,15R) via an ECD calculation (Figure 4). In addition, 16 known diterpenoids based on jatrophane, lathyrane, ingenane, abietane, and atisane skeletons were isolated and identified, including 2-epi-euphornin I (10), 28 euphoscopin J (11), 29 20-O-acetylingenol (12), 36 euphohelioscopin A (13), 35 (2R,3S,4S,7R,9S,11R,15R)-3-acetoxy-7,15dihydroxy-14-oxolathyr-5E,12E-diene ( 14), 35 altotibetol (15), 31 euphohelide A concurrently isolated by Yang et al (16), 37 helioscopinolide C (17), 38 helioscopinolide H (18), 39 3α-hydroxyjolkinolide A (19), 40 helioscopinolide D (20), 41 ent-3β,(13S)-dihydroxyatis-16-en-14-one (21), 42 13β-hydroxy-3,15-dioxoatis-16-ene ( 22), 42 euphonoid F ( 23), 43 ent-atisane- 3β,16α,17-triol (24), 44 and ent-atisane-16α,17-diol-3-one (25), 45 by comparing their NMR data with literature data.…”
Section: ■ Results and Discussionmentioning
confidence: 99%